Evaluation of The Implementation Policy of Menpan RB Regulation No. 3 of 2023 on The Bureaucratic Reform Index In The Indonesian National Army (TNI) - Anggoro Nurcholik Rusyianto; Reza Fathurrahman (Pelopor Publikasi Akademika, 2025)
This study analyzes the impact of the implementation of Permenpan RB Number 3 of 2023 on the Bureaucratic Reform Index within the Indonesian National Army (TNI). This regulation introduces 36 performance indicators consisting of 31 General RB indicators and 5 Thematic RB indicators. However, as an institution with a hierarchical and command-based structure, the TNI faces limitations in fulfilling indicators, where 15 General RB indicators and 2 Thematic RB indicators cannot be fulfilled because they are not in accordance with the main functions and characteristics of military institutions. The theoretical analysis of this study uses the policy evaluation theory from William N. Dunn (2015) to evaluate the effectiveness of policies in the context of military organizations. The results of the study show that although the TNI RB index has increased by 4.33 points compared to the previous year, there are still obstacles in its implementation. The inconsistency of indicators poses a risk of injustice in the evaluation of TNI performance. Therefore, it is necessary to adjust policies or more flexible evaluative mechanisms so that the bureaucratic reform system remains relevant to the characteristics of military organizations.